Psychological Reactions and the Process of Coping with Marital Infidelity in Couples: A Grounded Theory Research - Maryam Yaghoobi Tourki; Anahita Khodabakhshi-Koolaee; Mohammad Reza Falsafinejad (Kerman University of Medical Sciences, 2022)
Introduction: Marital infidelity as a traumatic event can endanger the married life of couples and lead them to divorce. This study aimed to identify the psychological reactions and the process of dealing with the disclosure of marital infidelity in the betrayed person.Methods: The present study was conducted using a qualitative method based on grounded theory. The research population included all married people living in Tehran, who had experienced marital infidelity in their marital life. The participants were 20 individuals who experienced marital infidelity and were selected through purposive sampling in 2019. The data were collected via semi-structured interviews with the participants and analyzed simultaneously using open, axial, and selective coding.Results: The reactions to the disclosure of marital infidelity were classified into two main themes (psychological reactions and physical reactions) and eight subthemes. The psychological reactions were shock and denial, anger and hatred, anxiety and rumination, feeling depressed and frustrated, cognitive errors, negative emotions, sleep disorders, and physical symptoms. The couples reacted to their spouse's infidelity under the influence of contextual and situational factors and decided whether to continue living together. These decisions ranged from forgiving or not forgiving the spouse, forgetting the infidelity, coercion to continue living together, and separation and divorce.Conclusion: The results of the study showed that with an awareness of the psychological reactions to the exposure of spousal infidelity and its contextual and situational factors, it is possible to understand the nature of problems and develop psychological interventions fitting couples' social and cultural conditions.